Development and Ergonomical Evaluation of Pedal Operated Coconut Dehusker (International Journal of Food and Nutritional Sciences, 2020)
Coconuts are cultivated in the world more than 95 countries. Coconuts are made upouter husk, middle shell and inner kernel. The coconuts husks are removed for further use. Theprocess of dehusking are remove outer part of coconuts which is called husk. Dehusking say thatin many ways like traditional tools, improved tools and pedal operated and other hydraulicoperated and power operated.